A Reconsideration of Gender Differences in Risk Attitudes - Filippin, Antonio; Crosetto, Paolo (Management Science, 2016)
This paper reconsiders the wide agreement that females are more risk averse than males. We survey the existing experimental literature, finding that significance and magnitude of gender differences are task specific. We gather data from 54 replications of the Holt and Laury risk elicitation method, involving about 7,000 subjects. Gender differences appear in less than 10% of the studies and are significant but negligible in magnitude once all the data are pooled. Results are confirmed by structural estimations, which also support a constant relative risk aversion representation of preferences. Gender differences correlate with the presence of a safe option and fixed probabilities in the elicitation method.This paper was accepted by John List, behavioral economics.